THE PROSECUTOR'S OFFICE IN PRE-PROSECUTION OF CORRUPTION CASE FILES WITH THE SUBJECT OF CORPORATE LAW - Iqbal, Muhammad; Syahri, Alvi; Sunarmi, Sunarmi; Ekaputra, M. (Inspiring Law Journal, 2025)
This study examines the role of the Prosecutor's Office in the pre-prosecution stage of corruption cases involving corporate legal entities and analyzes the mechanism for assessing formal and material completeness as a basis for prosecution feasibility. The increasing involvement of corporations in corruption cases poses challenges in proving corporate criminal liability and linking individual actions to corporate responsibility. This research uses normative legal methods with a statutory and conceptual approach through the analysis of the Criminal Procedure Code, the Law on the Eradication of Corruption, Supreme Court Regulation Number 13 of 2016, prosecutorial guidelines, and the doctrine of corporate criminal liability. The results of the study show that the Public Prosecutor plays a role as dominus litis in ensuring the completeness of the formal and material case files, including verification of corporate legality, fulfillment of criminal elements, attribution of liability, and sufficiency of legal evidence. The procedural law orientation that still focuses on individual actors is the main challenge. Therefore, the effectiveness of the pre-prosecution stage greatly determines the success of prosecution and legal certainty in corporate corruption cases.